FULFILLMENT OF EXERCISE NEEDS AMONG PREGNANT WOMEN DURING THE COVID-19 PANDEMIC - Afiyah, R. Khairiyatul; Kamariyah, Nurul; Wijayanti, Lono; Yhusnain, Juliatik Ragil (Nurse and Holistic Care, 2021)
Background: During the Covid-19 pandemic, many restrictions on almost all routine services including maternal and newborn health services. Some pregnant women are reluctant to go to health facilities for fear of contracting it. The exercise need fulfillment of pregnant women's is disrupted by a pandemic because the gym and the park are closed or fear of the virus exposure when exercising outside the home. Objective: The purpose of the study was to describe the exercise need fulfillment of pregnant women during the Covid-19 pandemic at Jagir Health Center Surabaya. Methods: This study used descriptive design. The sample was 40 pregnant women in the 2nd and 3rd trimester at Jagir Health Center Surabaya which obtained bytotal sampling technique. The research variable was the exercise need fulfillment of pregnant women during the Covid-19 pandemic. The research instruments was questionnaires and then data were analyzed using frequency distribution tables. Results: The study results found that out of 40 respondents, almost entirely pregnant women (82.5%) had poor exercise need fulfillment and 17.5% pregnant women had good exercise need fulfillment during the Covid-19 pandemic. Conclusion: The exercise need fulfillment of pregnant women during the Covid-19 pandemic was poor. The role of nurses can improve and maintain regular exercise in pregnant women. In education, it is important to emphasize that moderate amounts of exercise 150 minutes/week such as walking and yoga can be done in various ways, such as exercising indoors or viewing videos from YouTube, zooming during the Covid-19 pandemic to increase immunity.